Characterization of crystallographic texture of Zirconium alloy components by neutron diffraction - Malamud, Florencia; Moya Riffo, Alvaro Esteban; Vicente Alvarez, Miguel Angel; Vizcaino, Pablo; Li, M.J.; Liu, X.; Vogel, S.C.; Law, M.; Sumin, V.V.; Luzin, V.; Vasin, R.N.; Santisteban, Javier Roberto (Elsevier Science, 2018)
Fil: Malamud, Florencia. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina